Chiroptical Activities of Low‐Dimensional Lead‐Free Chiral Halide Perovskites with White‐Light Emission - Min‐Han Tsai; Chia‐Hsiang Chuang; Pei‐Hsuan Lo; Wei‐Yun Zeng; Chun‐Yao Huang; Lan‐Sheng Yang; Yu‐Chiang Chao (Small Science)
Chiral halide perovskites have attracted considerable attention due to their intrinsic chirality‐induced circular dichroism (CD), circularly polarized luminescence (CPL), and spin selectivity. However, chiroptical activities of low‐dimensional lead‐free chiral halide perovskites are hardly observed, especially for those with white‐light emission. Herein, lead‐free halide perovskites with different ratios of 0D Cs3Cu2I5 and 1D CsCu2I3 are realized. Chiroptical activities are introduced into these films by post‐treatment with r‐/s‐methylbenzylammonium iodide to realize lead‐free chiral halide perovskites. The absorption, photoluminescence, photoluminescence excitation, CD, and CPL spectra of these films are investigated. The Commission Internationale de L’Eclairage chromaticity coordinates (0.33, 0.33) are obtained when the excitation wavelength is 300 nm. Large Stokes shifts and broadband emission are observed and attributed to the presence of self‐trapped excitons. At room temperature, intrinsic chirality‐induced CD signals are observed without the application of an external magnetic field, indicating the presence of chirality in the low‐dimensional lead‐free chiral halide perovskites. Room‐temperature CPL is also observed from the low‐dimensional lead‐free chiral halide perovskites, but only from the Cs3Cu2I5 component. This is attributed to the fact that CsCu2I3 does not produce CPL and spin‐polarized excitons do not transfer from Cs3Cu2I5 to CsCu2I3.